Impressões de identidade : histórias e estórias da formação da imprensa gay no Brasil - Rodrigues, Jorge Luís Pinto (2007)
This work is the result of research on Impressions of Identity gathered from a number of periodicals of the gay press in Rio de Janeiro. Taking an interdisciplinary view, the thesis makes a comparative study between the verbal language (texts and articles) and the visual language (graphic elements that make up the pages) of these periodicals. From there, it reads the history and the stories of the construction of different gay identities. To deal with literature and design, the axis of the research was structured based on Cultural Studies, widening the subject of interdisciplinarity between areas. Design is a language which functions in the process of communication as an emitter whose enunciations are composed of ontological and historical relationships, symbolic, material and technical attributes, etc. Four periodicals were analyzed: the newspaper Lampião da Esquina, launched in 1978, was the first nationally-distributed periodical; the newspaper Nós por Exemplo, the only periodical which discussed AIDS and related concerns with a gay readership; the newspaper ENT& which, in spite of its short life span, was significant for this research; and finally the magazine Sui Generis which popularized the concept of GLS (Gays, Lesbians and Sympathizers) and introduced great changes in the field of graphic design in the gay press. I made a comparative study between what the text makes us see and what the image leads us to believe to delineate the design project of the representational regime of a specific historical and cultural moment. Not only do they narrate the social and political situation of a group at a certain time, but libertarian newspapers and magazines indicate the agreements which formulate the identity design of that group.